Traços e índices funcionais aplicados à larvas como ferramenta para a avaliação da reprodução de peixes nos gradientes espaciais de reservatórios - Gogola, Tatiane Mary (2018)
Based on the occurrence of fish larvae and analyzing the relationship of environmental variables and functional traits, we intend to evaluate the reproductive dynamics of the species along the Itaipu reservoir gradients. Assuming that the degree of influence of damming on fish reproduction follows the longitudinal gradient, and that this influence is more pronounced in the lacustrine region, we test the hypotheses: i) Environmental variables influence the spatial and temporal patterns of larval distribution functional groups of fish in reservoirs. ii) The reproduction of the fish in the lateral gradient follows the same trend as observed, if any, in the longitudinal gradient. Three arms of the left margin were evaluated, distributed along the longitudinal gradient of the reservoir (zones: lacustrine, transition and fluvial), whereas for the lateral gradient analysis, each arm was divided into three regions according to the distance of the influence of the reservoir, region I, near the central body, region II, intermediate between the reservoir and the lotic stretch and III near the lotic stretch of the arm. The collections were carried out monthly, between October and March, in the period from 2009 to 2016, totaling five periods. The samplings were carried out with plankton net, equipped with flow meter and in the nocturnal period. Samples of water were obtained for the verification of some environmental variables. In the laboratory, the larvae were identified at the lowest possible taxonomic level and evaluated in relation to some functional characteristics related to reproduction, feeding and occupation of the beds of the water column. In order to analyze the relation of environmental variables and functional traits, the RLQ and fourth-corner analyzes were performed. A total of 51,995 larvae were analyzed, with higher abundances in the lacustrine and transition zones and a larger number of taxa in the fluvial zone and region I. In general, turbidity and precipitation influenced positively the migratory taxa, mainly in period V and period IV was negatively influenced by the quota of the reservoir favoring sedentary species and adapted to the lentic environments. The migratory species were also related to the differentiation of the fluvial zone. The RLQ performed separately for each zone of the longitudinal gradient indicated a differentiation of region I, and in each arm the environmental variables influenced in a different way. Thus, we can conclude that the composition of the functional groups of the fish species that reproduce in the Itaipu reservoir changes along the longitudinal gradient, with influence of precipitation, turbidity and elevation of the quota for the migratory species and smaller quotas for the sedentary ones, corroborating with our first hypothesis. In relation to the lateral gradient, this differentiation was not so evident, and we can conclude that the reproduction of the species in the lateral gradient is more related to its position in the longitudinal gradient and, thus, rejecting our second hypothesis.